Development of frozen grated cassava paste as a base for Malaysian traditional cakes (PDF boleh COPY) - Gan, Horng Eng (2008)
The optimum formulation for production of baked cassava cake i.e. a type of Malaysian traditional cake was determined using response surface methodology (RSM). The effects of amount of ingredients such as sugar (10-30%) and coconut milk (15-35%) on the instrumental textural characteristics and sensory acceptance of cakes were investigated. Based on superimposed plots, the basic formulation for production of baked cassava cake with desired sensory quality was obtained by incorporating 25 % of white granulated sugar and 20 % of coconut milk to the basic formulation. Physicochemical analyses were carried out to evaluate the changes in the quality of frozen cassava paste whereas; instrumental measurements and sensory tests were performed to assess the quality of baked cassava cake at monthly interval for a period of six months during frozen storage. The drip loss was increased initially for the three months of storage and decreased slightly in the following month onwards. The prolonged frozen storage had led to a brighter frozen grated cassava paste. The ice crystals formation and enlargement had negative impact on textural properties i.e. firmness and rheological of the cassava paste during frozen storage. When viewed under an electron microscope, it was confirmed that the cell wall structures and membranes of cassava paste were damaged during the frozen storage. Furthermore, both the changes in the textural profile and sensory attributes of baked cassava cake had also showed similar trend of results with the instrumental data and this further supported t the changes in the quality of baked cassava cake was solely due to the freezing process, frozen storage and subsequent thawing. The degree of acceptability of all the attributes was also reduced after six months of frozen storage and the recommended storage period for frozen grated cassava paste was up to four months. The effects of different concentration of xanthan gum (0 %, 0.2 %, 0.4 %, 0.6 % and 0.8 %, w/w) on frozen grated cassava paste were also studied. Results showed that xanthan gum had effectively reduced the drip loss and at the same time improved the textural properties i.e. firmness and rheological parameter of the cassava paste during frozen storage. However, the degree of acceptability for the sensory attributes of baked cassava cake were reduced as the concentration of xanthan gum was increased. Hence, the most suitable concentration of xanthan gum to be added was 0.2% w/w. The effect of five successive freeze-thaw cycles on physicochemical, textural and rheological properties as well as sensory qualities of frozen grated cassava paste was studied. The drip loss was significantly higher in sample that was subjected to five freeze-thaw cycles when compared with the control (zero cycle). The firmness and rheological properties of the cassava paste as well as the degree of acceptability of the baked cassava cake was decreased gradually as the number of cycles was increased.